“Dubula ibhunu” (shoot the boer): A psycho-political analysis of farm attacks in South Africa - Pretorius, Joelien (PINS-Psychology in Society, 2025)
Post-colonial archetypes in the collective unconscious of South African society have actualised themselves powerfully in the discourses that have usurped the framing of what has come to be called “farm attacks” in South Africa. These attacks are often a grotesque enactment of a violent script that blurs crime and post-apartheid comeuppance on the farm as mythical representation of the post-apartheid state. Framing these attacks as a Boer Genocide or justifying them as a form of colonial struggle/restitution remains rooted in totalising Afrikaner and black nationalisms respectively that not only renders the potential for addressing/redressing this violence barren, but actually inform it. Post-colonial psychology offers a lens to analyse the psycho-political underpinnings of this violence and its framing.